Tourist Satisfaction: An Empirical Study of Kokernag - Mohammad Shafiq Ur Rehman, Dr.Pradyuman Singh Rathore (International Journal of Advanced Science and Technology, 2020)
Tourism is the fastest growing industry in the world which is playing a vital role in economic development and in generating employment opportunities across the globe. Kashmir Himalayas has achieved world famous tourist destinations. The rainbow trout farms, gardens, fresh water spring, vast stretches of green forests and pastoral land represents the famous destination in south Kashmir known as Kokernag. For the fame of any tourist destination, tourist satisfaction is very important. Therefore, in order to study the tourist satisfaction towards the tourism services offered to tourists in Kokernag, an empirical study was conducted in which, besides the tourist demographic profile, 25 study objective oriented variables were asked to randomly selected 110 tourists in Kokernag; out of total number of respondents, 78 were domestic and 32 from foreign lands. After using 5 Point Likert Scale, in questionnaire, for getting responses from tourists, their responses was measured by percentage, mean and Std. Dev. techniques by SPSS software version 16. The study results reveal that tourists are satisfy with the tourism services offered in Kokernag. Almost, the satisfaction graph is higher in all variables; however, the dissatisfaction portion is either lower or invisible in the all graphs. The variables like, natural beauty, unspoiled nature, no food problems, accessibility, accommodation quality, and tourist information availability are satisfying tourists fully with a few numbers of neutral tourists. Moreover, the findings indicate that around 80% tourists are satisfied followed by around 20% of dis-satisfied and neutral tourists. Therefore, less than 20% dis-satisfied tourists is not a matter of worry but, in spite of this high tourist satisfaction, enhancement of tourism services is very essential for maintaining the tourist satisfaction and increasing the tourist loyalty in Kokernag for future existence.